Respecting life and death in the 90's [videorecording] - O'Connor, John Cardinal (Daughters of St. Paul, 1996)
John Cardinal O'Connor, Archbishop of New York provides facts in this talk about life/death issues of the 1990's. Addressing the respect Life Institute at St. Joseph's Seminary in Yonkers, New York, Cardinal O'Connor unmasked the unethical legal situation of the nation.